Neglected Tropical Diseases among Two Indigenous Subtribes in Peninsular Malaysia : Highlighting Differences and Co-Infection of Helminthiasis and Sarcocystosis - Soo, Ching Lee; Romano, Ngui; Tiong, Kai Tan; Roslan, Muhammad Aidil; Yvonne Ai, Lian Lim (PLOS, 2014)
Soil-transmitted helminth (STH) infections have been documented among these minority groups since 1938. However the prevalence of STH is still high among these communities. Most studies tend to consider the Orang Asli (indigenous) as a homogenous group. In contrary, different subtribes have their own cultural practices. To understand this variation better, we studied the prevalence and associated factors of STH and other gut parasitic infections among two common subtribes (i.e. Temuan and Temiar). Results showed that the prevalence of the overall STH infections was higher in the Temuan subtribe (53.2% of 171) compared to the Temiar subtribe (52.7% of 98). Trichuris trichiura (46.2%) was the most prevalent parasite in the Temuan subtribe, followed by Ascaris spp. (25.7%) and hookworm (4.1%). In contrast, Ascaris spp. (39.8%) was more prevalent among the Temiar subtribe, preceded by T. trichiura (35.7%) and finally hookworm (8.3%). There were also co-infections of helminthiasis and intestinal protozoa among both Temuan and Temiar subtribes with rates being three times higher among the Temiar compared to Temuan. The most common co-infection was with Entamoeba histolytica/dispar/moshkovskii (n = 24; 24.5%, 16.0–33.0), followed by Giardia spp. (n = 3; 3.1%, 20.3–6.5). In Temuan, STH infection individuals were also infected with Entamoeba histolytica/dispar/moshkovskii (n = 11; 6.4%, 5.0–13.8), Cryptosporidium spp.(n = 3, 1.8%, 20.2–3.8) and Giardia spp. (n = 2, 1.2%, 20.4–2.8). In comparison, there was no Cryptosporidium spp. detected among the Temiar. However, it was interesting to note that there was an occurrence of co-infection of intestinal helminthiasis and sarcocystosis (intestinal) in a Temiar individual. The last report of sarcocystosis (muscular) among the Orang Asli was in 1978. The present study highlighted the importance of understanding the variation of infections amongst the different Orang Asli subtribes. It is vital to note these differences and use this knowledge to customise effective control measures for the various subtribes.